Targeting GPCRs Against Cardiotoxicity Induced by Anticancer Treatments - Audebrand, Anais; Désaubry, Laurent; Nebigil, Canan G. (Frontiers in Cardiovascular Medicine, 2020)
Novel anticancer drugs such as targeted therapies and immune checkpoint inhibitors have greatly improved the management of a wide spectrum of malignancies. However, both conventional and novel anticancer drugs-induced cardiotoxicity still remains as a critical issue. Cardiotoxicity induced by anti-cancer drugs comprise vasospastic and thromboembolic ischemia, dysrhythmia, hypertension, myocarditis and left ventricular (LV) dysfunction, leading to heart failure. Importantly, none of the strategies to prevent cardiotoxicityfrom anticancer therapies is completely safe and satisfactory. Certain clinically used cardioprotective drugs can even contribute to cancer induction. Since G protein coupled receptors (GPCRs) are target of forty percent of clinically used drugs, here we discuss the newly identified cardioprotective agents that bind GPCRs of adrenalin, adenosin, melatonin, Ghrelin, Galanin, Apelin, prokineticin and cannabiodiol. We hope to provoke further drug development studies considering these GPCRs as potential targets to be translated to treatment of human heart failure induced by anticancer drugs.